Business Model Canvas Non Government Organization (NGO) (Case Study : Rimbawan Muda Indonesia) - Lukmi Ati; Lukman M. Baga; Arif Satria (School of Business, IPB University (SB-IPB), 2019)
Rimbawan Muda Indonesia (RMI) is an independent non-profit organization (NGO) that focuses on natural resources and environmental issues. This NGO aims to develop the conservation of natural resources. In order to achieve the vision and mission, the organization is not compatible with conducting the business model optimally, hence new strategies are needed to fix the business model. The aim of this research: (1) To identify and obtain the map (portrait) of the current RMI business model; (2) To analyse the SWOT of each element in RMI’s business model; (3) To design an alternative strategy as an improvement on the current business model. This research used the combination of the Business Model Canvas (BMC) approach and SWOT matrix analysis. According to the analysis results, it could be concluded that RMI needs to conduct a business model improvement on nine BMC elements that consists of eight formulation alternative strategies including: 1) creative fund-raising strategies to the donor(s) that focus on youth and women issues, 2) one issue focus, 3) live-in community organization, 4) a fund-raising strategy by self-promotion space roadshows and attending donor events, 5) Capacity building through knowledge sharing amongs staff both internal and inter-network, 6) Outside Java Networking development, 7) Improvement on relationship to donors through e-mails intensively and on roadshows, 8) Donor visit due to the stop of collaboration. Mentioned strategy alternatives are elaborated on the form of improvement programs that will be described in each element of business model canvas.Keywords: business models, BMC, NGO, SWOT, RMI